The five : the untold lives of the women killed by Jack the Ripper - Rubenhold, Hallie (Mariner Books, Houghton Mifflin Harcourt, 2020)
Researched portraits of the five women murdered by Jack the Ripper in 1888 reveal each victim's historically relevant and diverse background while discussing the cultural and gender disadvantages that made them vulnerable.